Video Company Profile Bengkel Benson - Bambam Julianto; Muhammad Ardiansyah (National Conference for Community Service Project (NaCosPro), 2023)
Benson Workshop is one of the quality workshops in Karimun City. In carrying out the process, Benson Workshop is under the leadership of Mr. Herman. Benson's workshop is located at Jalan Ahmad Yani RT 003 RW 006, Meral Kota, Tanjung Balai Karimun, Riau Islands. Currently, the workshop does not have a company profile video so a company profile video is needed on it. Company Profile videos are able to attract customer attention because the content is made interesting. With the company profile video, customers can more easily get to know partners, so that what consumers need is easier to achieve. Data collection on the implementation of KP activities was carried out using interview method and MDLC method . . The output of this PkM implementation is an interesting and easy-to-understand Company Profile Video and in accordance with User Requipment. The stages of this KP activity include the stages of output design, implementation of outputs, and evaluation of outputs. The resulting output received a positive response from partners. The output of this KP activity is expected to help partners become workshops that are better known by the community